The Assessment of the Use of Eco-Friendly Nets to Ensure Sustainable Cabbage Seedling Production in Africa - Muleke, Everlyne; Saidi, Mwanarusi; Itulya, Francis; Martin, Thibaud; Ngouajio, Mathieu (Agronomy (Basel), 2013)
High seed cost accompanied by poor germination and seedling performance renders cabbage nursery and field production enterprises unsustainable to many small-scale growers in tropical and sub-tropical countries. In most nurseries, adverse ecological conditions and pest damage are among the major factors responsible for poor seedling performance. The objective of this study was to test the potential use of eco-friendly net (EFN) covers as a low cost technology for sustainable cabbage seedling production. The study was a two-season experiment conducted using a randomized complete block design with five replications and two treatments. Treatments were: the standard open field transplant production (control) and transplant production under 0.4 mm mesh polyethylene net covering. EFN covering increased both temperature and relative humidity, enhanced seedling growth and reduced insect pest damage. Seed germination and seedling emergence were under the net covering earlier. Higher seed germination and seedling survival were recorded under the EFN treatment, indicating a potential for reducing the seed requirement per unit area of cabbage production. Seedlings grown under the nets had higher stomatal conductance and leaf chlorophyll content; furthermore, they grew taller, with more leaves within a shorter period of time compared to the control seedlings. The use of EFN in cabbage nurseries offers a sustainable technology for enhancing seedling performance by reducing pest infestation, thereby lowering production cost and improving the grower’s income.